Unveiling Fraud: The Hexagon Theory's Revolutionary Approach to Detecting Financial Statement Manipulations - Oktavia, Reni; Rinaldo, Nindya Saphira Maharani (Universitas Pendidikan Indonesia, 2024)
This study aims to determine and empirically prove how the influence of the fraud hexagon theory on financial statements. The research encompasses a population of non-financial S.O.E.s, utilizing secondary data and logistic regression analysis via S.P.S.S. software. A purposive sampling technique was employed, resulting in 102 valid samples for analysis. The study reveals that the opportunity, as indicated by the nature of the industry, significantly and positively impacts financial statement fraud. Conversely, pressure indicated by Return on Assets (ROA), changes in directors reflecting capability, changes in public accountants reflecting rationalization, C.E.O. duality reflecting arrogance, and government projects reflecting collusion do not exhibit a significant effect on financial statement fraud. This research demonstrates that a high ratio of changes in receivables to income increases the likelihood of fraud. Moreover, it confirms the Fraud Hexagon Theory's applicability in detecting a company's propensity for financial statement fraud. The novelty of this study lies in the inclusion of the government project variable (collusion), using National Strategic Project criteria as an indicator, which has yet to be extensively explored in prior research.